About the origin of the scientific academies - Cecon, Kleber [UNESP] (Sociedade Brasileira de Historia da Ciencia, 2021)
The main focus of this work is to briefly expose about the origins of the so called “scientific” communities, societies or academies. What is an academy? What kinds of academies or societies were created? When the scientific societies started? What defines them as such? Far from give a definitive answer to these questions, this article considers some possibilities. In doing so, it comments about the origin of the term “academy” in ancient Greece, the cultural European academies, and finally some peculiarities of the scientific societies of the seventeenth-century, like hermeticism and specification.
Sobre a origem das academias científicas
Keywords: hermeticism; scientific academies; scientific communities; scientific publications; scientific societies